Modifikasi Karakteristik Edible Film Pati Aren Melalui Proses Retrogradasi dan Heat Moisture Treatment - Pranoto, Yudi (2009)
Arenga pinata starch is potential to be formed into an excellent film matrix due to its high amylose content, around 30.05%. This makes the film formed to be compact (rigid), but a bit brittle. In addition, starch gel characteristic can be improved by retrogradation and heat moisture treatment (HMT). The objective of this study was to modify characteristic of arenga pinata starch film by retrogradation and HMT. Edible film was prepared from 3% (w/v) of the starch solution added with glycerol as plasticizer at 30% (w/w). The solution was heated to 80oC for 15 min by mixing to ensure dissolution of starch. The solution was then poured onto a plastic plate and retrograded by keeping at the temperature of 4oC at varying time 0.5; 1 and 1.5 h. Then, it was HMT treated by keeping in the oven at 110oC for varied time of 0.5; 1 and 1.5 h. Finally, the treated sample was dried in an oven dryer at 50oC to attain moisture content of 12%, while control was the same edible film prepared without retrogradation and HMT treatments. The edible films obtained were analyzed for the thickness, tensile strength, elongation and solubility properties. The results indicated that retrogradation and HMT did not significantly affect the thickness and elongation, but they significantly affected tensile strength and solubility. With the tensile strength ranging from 2.98 to 6.10 MPa, the value increased with the longer time of HMT. On contrary, the longer retrogradation and HMT time decreased solubility of edible film, ranging 14.46 – 21.06%. The best arenga starch film was resulted by retrogradation time and HMT time of 1 h and 1.5 h, respectively. It revealed the highest tensile strength at 6.19 MPa, dissolution value was 14.88%, elongation value was 12.58% and the thickness was 83.70 µm.